When Body, Emotion, and Translation Meet: A Proposal for a Reader- and Translator-Oriented Approach to Translation - Constantino Reyes, Julia (TTR, 2019)
This article attempts to explore, in a theoretical manner, some possible ways in which translation may question binaries and authority by creating links between sex-gender non-conforming experiences, and translation. I suggest a flexible, reader-oriented and translator-oriented approach to translation based on performativity, narrativity, theory of emotions and affect theory, feminist theory, and queer theory that can possibly contribute to the transformation of some still rigid expectations about translation as a process, a product, and a phenomenon. The article discusses how emotions and performativity elements used by feminist and queer translation may contribute to a reconceptualization of translation based on a questioning and undermining of binary thinking—and of related concepts such as equivalence, fidelity, unity, coherence, and homogeneity—through repetition, difference, and provisionality. A central point is that the ambiguity that can arise from breaking away from binary thinking in translation and in sex-gender non-conforming bodies and experiences through mechanisms of performativity and of emotions as cultural practices can become an ethical space of resistance and activism. Such a space may denounce the arbitrariness of meaning-producing practices, propose other sites of meaning and knowledge, and construct more flexible narratives. This may be accomplished through the construction of productive shame and discomfort, emotions which are impressed on the body. These emotions can become a link between reader and translator thereby contributing to the transformation of translation and of translation-reading expectations, paradigms, and practices.